P-19 Transepithelial PTK/limited non topoigraphic PRK combined with corneal crosslinking for keratoconus. (26th May 2022) - Mukherjee, Hatch; Pipis, Spyros; Yang, Yunfei; Santos, Adriana
Abstract : *Correspondence - Hatch Mukherjee: hatch.mukherjee@gmail.com Objective: To evaluate the outcomes of combined excimer laser PTK/limited PRK combined with corneal crosslinking in the management of keratoconus. Methods and Analysis: Data were analysed from a retrospective cohort of eyes undergoing PTK epithelial removal or limited PRK combined with corneal crosslinking. Patients undergoing PRK were either contact lens intolerant or were considering alternate surgical therapy including corneal transplantation. Data included uncorrected and best corrected vision, refraction and OCT topographic findings. Treatments were performed using a TECHNOLAS® TENEO™ 2 (Bausch & Lomb) and CXL with Avedro KXL (Glaukos) according to a modified protocol. Results: 24 eyes were treated using combined Excimer laser PTK or limited non-topographic transepithelial PRK depending on intervention protocol with >3 month follow-up. Postoperative best corrected visual acuity improved by a mean of 0.42 LOGMAR units (SD 0.37, range 0.1 to 1.4) (p<0.005). All eyes had improvement of BCVA. Mean absolute spherical refractive error decreased by 0.56 D (SD 1.26, range -2.5 to 2) (p<0.05). Postoperative spherical error increased in a few cases (3/24, 12%) Mean absolute refractive cylinder decreased by 1.46D (SD 2.3 range -4.75 to 7) (p<0.05). Limited increase of astigmatism occurred in 2 (8, 3%) cases. There were no postoperative complications noted. Conclusion: PTK/limited non topographic PRK combined with CXL may offer improvement to corrected visual acuity compared to CXL alone.